PERSPECTIVES OF THE SOLAR ENERGY DEVELOPMENT AND ITS EFFECT ON THE OPERATION OF ELECTRICAL ENERGY SYSTEMS - Buslova, Naina; Dmitriyev, Valerii (Sworld-Us Conference proceedings, 2023)
The work deals with issues of solar energy, which is currently developing at a rapid pace. This is facilitated by an inexhaustible resource and the absence of environmental pollution. The positive impact of solar installations on the operation of electric